Case report of a 28 years old woman with lepromatous leprosy mimicking systemic lupus erythematosus - Wijaya, Edward; Komarasari, Eka; Esti, Prima Kartika (Explorer Front, 2024)
Background: Leprosy has been known as the greatest imitator disease that can mimic a disease condition, including autoimmune disease. This case report aims to demonstrate and remind healthcare providers that leprosy infection may manifest with various autoimmune phenomena reminiscent of classic autoimmune disease, including systemic lupus erythematosus (SLE), and to prevent delayed treatment and further complications. Case report: A 28-year-old female patient with ulcers all over her body and amputation of her fingers and toes. Based on the positive antinuclear antibodies (ANA) test results, weak positive ANA profile band, anticardiolipin antibodies immunoglobulin M (ACA IgM), and complement C4 test, the patient has been diagnosed with systemic lupus erythematosus (SLE) since eleven years ago. There was no improvement during SLE therapy as the years passed. The patient developed leprosy symptoms such as madarosis, saddle nose, and facies leonine. Slit skin smear for leprosy acid-fast bacilli (AFB) from forehead and chin showed bacterial index +6, skin biopsy examination concluded lepromatous leprosy with bacterial index +5, and IgM anti-PGL-1 serological test examination 3185 u/ml. She was treated with steroids at the hospital and multidrug therapy for multibacillary leprosy (MDT MB) for one year. She had significant improvement after receiving medication. Conclusion: The diagnosis of leprosy is delayed because of the clinical similarities between the disease and SLE. The clinicians should know leprosy-specific symptoms to avoid inaccurate diagnoses and treatment delays.